Nanomedicine: A Diagnostic and Therapeutic Approach to COVID-19 - Sharma, Arjun; Kontodimas, Konstantinos; Bosmann, Markus (Frontiers in Medicine, 2021)
The SARS-CoV-2 virus is causing devastating morbidity and mortality worldwide. Nanomedicine approaches have a high potential to enhance conventional diagnostics, drugs and vaccines. In fact, lipid nanoparticle/mRNA vaccines are already widely used to protect from COVID-19. In this review, we present an overview of the taxonomy, structure, variants of concern, epidemiology, pathophysiology and detection methods of SARS-CoV-2. The efforts of repurposing, tailoring, and adapting pre-existing medications to battle COVID-19 and the state of vaccine developments are presented. Next, we discuss the broad concepts and limitations of how nanomedicine could address the COVID-19 threat. Nanomaterials are particles in the nanometer scale (10-100 nm) which possess unique properties related to their size, polarity, structural and chemical composition. Nanoparticles can be composed of precious metals (copper, silver, gold), inorganic materials (graphene, silicon), proteins, carbohydrates, lipids, RNA/DNA, or conjugates, combinations and polymers of all of the aforementioned. The advanced biochemical features of these nanoscale particles allow them to directly interact with virions and irreversibly disrupt their structure, which can render a virus incapable of replicating within the host. Virus-neutralizing coats and surfaces impregnated with nanomaterials can enhance personal protective equipment, hand sanitizers and air filter systems. Nanoparticles can enhance drug-based therapies by optimizing uptake, stability, target cell-specific delivery and magnetic properties. In fact, recent studies have highlighted the potential of nanoparticles in different aspects of the fight against SARS-CoV-2, such as enhancing biosensors and diagnostic tests, drug therapies, designing new delivery mechanisms and optimizing vaccines. This article summarizes the ongoing research on diagnostic strategies, treatments and vaccines for COVID-19, while emphasizing the potential of nanoparticle-based pharmaceuticals and vaccines.